Protective Role of Magnesium Malate and Vitamine E Against Aluminium Chloride Toxicity on Antioxidant Enzymeactivity in Albino Rats - Savithri Y.; Ravi Sekhar P.; Kumari, D. Aruna (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The present work was aimed to assess the effect of vitamin E (vit. E) and magnesium malate against aluminium chloride (AlCl3) toxicity on antioxidant enzymes xanthine oxidase (XOD), super oxide dismutase (SOD) and catalase (CAT)activities in liver tissues of albino rats. Rats were divided in to five groups, group I received normal saline, group II administered orally with AlCl3 (7.5 mg kg bw), group III received magnesium malate (5.0 mg/ kg bw), group IV received with AlCl3 and vitamin E(10 mg kg bw) and group V with AlCl3, Magnesium malate and vit E. The antioxidant enzyme XOD activity levels were increased in AlCl3 treated animals and gradual decrease was observed in magnesium malate and vit. E treated animals, SOD activity was decreased in AlCl3 treated animals where increase was observed in magnesium malate and vitamin E treated animals, the catalase (CAT) activity was decreased in AlCl3 treated animals where increase was observed in magnesium malate and vitamin E (vit-E) treated animals. The results indicated that the toxic effect of AlCl3 could be mediated through modifying antioxidant enzyme activity in rat liver which may lead to impaired function. The combined treatment with magnesium malate and vit E was effective in the restoring the studied parameters near to the normal.